2014
DOI: 10.1586/14787210.2015.990383
|View full text |Cite
|
Sign up to set email alerts
|

Phage approved in food, why not as a therapeutic?

Abstract: Bacterial resistance is not only restricted to human infections but is also a major problem in food. With the marked decrease in produced antimicrobials, the world is now reassessing bacteriophages. In 2006, ListShield™ received the US FDA approval for using phage in food. Nevertheless, regulatory approval of phage-based therapeutics is still facing many challenges. This review highlights the use of bacteriophages as biocontrol agents in the food industry. It also focuses on the challenges still facing the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 79 publications
0
43
0
1
Order By: Relevance
“…Recently, with the emergence of multidrug resistant strains and the highthroughput sequencing abilities, the risk of using phages with unwanted genes has been greatly reduced. Phage therapy is being considered, again, for use both in the food industry and in medicine (25). In addition, several reports showed that phage therapy improved (26)(27)(28), and in some cases was even more successful than (29,30), antibiotic treatment.…”
mentioning
confidence: 99%
“…Recently, with the emergence of multidrug resistant strains and the highthroughput sequencing abilities, the risk of using phages with unwanted genes has been greatly reduced. Phage therapy is being considered, again, for use both in the food industry and in medicine (25). In addition, several reports showed that phage therapy improved (26)(27)(28), and in some cases was even more successful than (29,30), antibiotic treatment.…”
mentioning
confidence: 99%
“…Phages, as “our enemy’s enemy,” are potential weapons against drug-resistant pathogens [16, 17]. Some phage products have already been approved by the FDA as food biopreservatives, such as ListShield and ListexP100 [18]. The Phagoburn clinical study, supported by several European countries, was conducted to assess the safety, effectiveness, and pharmacodynamics of two therapeutic phage cocktails to treat E. coli and P. aeruginosa burn wound infections [19].…”
Section: Discussionmentioning
confidence: 99%
“…Food-borne infections in the United States alone have been estimated to cause ~76 million illnesses, more than 300,000 hospitalizations and 5000 deaths each year [1]. Moreover, food contamination could result in a loss of 25% of food produced every year [2]. Bacterial pathogens, such as Escherichia coli O157:H7, Salmonella , Campylobacter jejuni , and Listeria monocytogenes , are the leading causes of these bacterial foodborne illnesses [3].…”
Section: Introductionmentioning
confidence: 99%